The impact of a faculty development program: evaluation based on the self-assessment of medical educators from preclinical and clinical disciplines - YEGEN, BERRAK; SARIKAYA, ÖZLEM (AMER PHYSIOLOGICAL SOC, 2010)
Sarikaya O, Kalaca S, Yeg. en BC,, Cali S. The impact of a faculty development program: evaluation based on the self-assessment of medical educators from preclinical and clinical disciplines. Adv Physiol Educ 34: 35-40, 2010

doi: 10.1152/advan.00024.2010.-Self-assessment tools have previously been used to assess the impact of a faculty development program on the teaching skills of medical educators. In this study, we aimed to assess the impact of a faculty development program on the teaching performances of faculty members in relation to their medical disciplines and academic positions. A faculty-training program consisted of training skills and student assessment instruments courses. The impact of the program was evaluated by self-reporting of faculty members (a total of 225 reports) 1-2 yr after the program. Both courses were found to be beneficial by nearly all of the attendants. Clinicians benefited more from some topics in the student assessment course and could apply the structured learning and assessment guides, structured oral examination, and objective structured clinical examination more efficiently than their peers from preclinical departments. In conclusion, the results demonstrated that the participants of the faculty development program modified their teaching activities according to the demands of their clinical practice. The correlations between the benefits and behavioral changes were statistically significant.
Keywords: training skills; assessment guides; structured oral examination; objective structured clinical examination; SKILLS; IMPROVEMENT; TEACHER